2023
DOI: 10.1002/ams2.817
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID‐19 pandemic on epidemiology, treatment, and outcome of major trauma in Japan in 2020: a retrospective observational nationwide registry‐based study

Abstract: Aim The nationwide impact of the coronavirus disease (COVID‐19) pandemic on major trauma in Japan is unknown. The nationwide registry‐based data of the Japanese Trauma Data Bank were analyzed to elucidate the impact of COVID‐19 on the epidemiology, treatment, and outcomes of major trauma patients. Methods Among patients transported directly from the injury site by ambulance with an Injury Severity Score of ≥16, we compared patients managed from April to December in 2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…An increase in mean age was observed in a study of major trauma admissions in four hospitals in Finland presented by Riuttanen et al [47]. On the other hand, in a large database study of trauma admission during the COVID-19 pandemic in Japan, a significant difference in mean age was not reported [48]. This study analyzed only major trauma and assessed the influence of COVID-19 over a longer time period than in our study.…”
Section: Median Agecontrasting
confidence: 44%
See 1 more Smart Citation
“…An increase in mean age was observed in a study of major trauma admissions in four hospitals in Finland presented by Riuttanen et al [47]. On the other hand, in a large database study of trauma admission during the COVID-19 pandemic in Japan, a significant difference in mean age was not reported [48]. This study analyzed only major trauma and assessed the influence of COVID-19 over a longer time period than in our study.…”
Section: Median Agecontrasting
confidence: 44%
“…In the study by Ghafil et al, trends in trauma admissions (14,000 admissions) during the COVID-19 pandemic in 15 trauma centers in Los Angeles Country were analyzed, and they found no significant differences in transportation injuries and falls compared with the same period in 2020 [51]. Ojiima et al assessed the impact of the COVID-19 pandemic on major trauma in Japan, and a significant decrease in motorvehicle collision (MVC) injuries was reported during the lockdown period [48]. Moyer also reported a statistically significant reduction in cases only in MVCs among major trauma patients in France [41].…”
Section: Injury Mechanismsmentioning
confidence: 99%
“…In contrast, a systemic review of severe trauma during the restriction policy period in the first wave of the COVID-19 pandemic reported that the number of severe trauma patients decreased during this wave of the COVID-19 pandemic, but severity and mortality remained the same ( 22 ). Another study analyzing a multicenter trauma registry in Japan reported that time related to prehospital care increased during the pandemic in 2020, but in-hospital mortality did not change ( 23 ). As more patient occupy treatment space at medical facilities, emergency patients will have to be transported by ambulance to distant medical facilities because the facilities will not be able to accept excess patients.…”
Section: Discussionmentioning
confidence: 99%